2022
DOI: 10.1093/jambio/lxac079
|View full text |Cite
|
Sign up to set email alerts
|

Dietary potential probiotics and enzymes complex modulates the performance and rumen microbiota in weaned goats

Abstract: Aims This trial was performed to investigate the effects of combined feeding of Candida utilis CICC 31170, Bacillus coagulans R11, and Lactobacillus acidophilus NCFM and a multi-enzyme complex on the growth performance, immune parameters, feed digestibility, and rumen microbiota of weaned goats. Methods and Results Thirty weaned goats were randomly divided into CON, PRB, and COB groups and fed different diets. End weight and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Bacillus coagulans is a gram-positive, facultative anaerobic, nonpathogenic, endospore-forming, lactic acid-producing bacteria and has been granted Generally Recognized as Safe (GRAS) status by the US Food and Drug Administration (FDA) ( Cao et al, 2020 ). Several studies have demonstrated the beneficial effects of this probiotic species when administered as a feed additive or dietary supplement to livestock, aquaculture and human health ( Hung et al, 2012 ; Gu et al, 2015 ; Izadi et al, 2020 ; Lu et al, 2023 ). In preclinical studies, B. coagulans has demonstrated improved body weight, enhanced average daily gain, improved feed conversion ratio, antioxidant capacity, immunity function and gut health in broiler chickens ( Hung et al, 2012 ; Zhang et al, 2021 ; Cao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus coagulans is a gram-positive, facultative anaerobic, nonpathogenic, endospore-forming, lactic acid-producing bacteria and has been granted Generally Recognized as Safe (GRAS) status by the US Food and Drug Administration (FDA) ( Cao et al, 2020 ). Several studies have demonstrated the beneficial effects of this probiotic species when administered as a feed additive or dietary supplement to livestock, aquaculture and human health ( Hung et al, 2012 ; Gu et al, 2015 ; Izadi et al, 2020 ; Lu et al, 2023 ). In preclinical studies, B. coagulans has demonstrated improved body weight, enhanced average daily gain, improved feed conversion ratio, antioxidant capacity, immunity function and gut health in broiler chickens ( Hung et al, 2012 ; Zhang et al, 2021 ; Cao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cellulases and xylanases are the most widely used exogenous enzymes in animals and play important roles in nutrient utilization. In addition, enzyme supplementation has a potential effect on the composition and metabolic capacity of rumen microbes ( 18 , 19 ), which can alter the composition of microbial communities ( 20 , 21 ) and improve rumen fermentation and health ( 22 ). In the actual production process, most farmers use a sloppy meat farming model to obtain higher economic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, few experiments have evaluated dietary supplementation with phytase [12], protease [13], or glucoamylase [14,15]. It should be noted that there have been studies focusing on the supplementation of enzyme complexes [16,17]. In non-ruminants, M-E preparations are frequently used [18,19], with blends formulated on a ration of indigestible components to obtain more nutrients [20].…”
Section: Introductionmentioning
confidence: 99%